Effectiveness of Sequences of Classroom Training for Welfare Recipients: What works best in West Germany? - Katharina Dengler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Sequences of active labour market programmes (ALMPs) may be part of an intensified activation strategy targeting hard-to-place individuals who may be long-term unemployed and who may encounter extreme difficulty in finding jobs. Such sequences are very common among welfare recipients in Germany, but most studies only evaluate either single ALMPs or unemployed individuals first ALMP. Thus, I analyse the effects of different sequences of classroom training, unemployment benefit II (UB II) receipt and One-Euro-Jobs for West German men and women on different labour market outcomes. Using rich administrative data and a dynamic matching approach, I can control for dynamic selection problems that occur during a sequence. My results show that two classroom trainings are more effective than two periods of UB II receipt in helping welfare recipients find regular employment, especially among West German women. In some cases, avoiding participation in multiple programmes is preferable: participation in two classroom trainings has mostly no beneficial effects over participation in one classroom training in the second period only and participation in one classroom training followed by a One-Euro-Job has mostly no beneficial effects over participation in a One-Euro-Job in the second period only. Moreover, immediately assigning individuals to classroom training is more effective than waiting and assigning them to classroom training in the second period (the effects of timing) because of the positive effects on avoiding UB II receipt (work-test function). However, evidence for programme careers or stepwise integration is only observed for the sequence of two classroom trainings versus the sequence of two periods of UB II receipt.
Keywords: C13; I38; J68; 330